Penerapan Direct Interaction Terhadap Peningkatan Hasil Belajar Jurus Tunggal Baku Tangan Kosong dalam Pembelajaran Pencak Silat - Akhmad Sobarna; Sumbara; Gugun Gunawan; Henry; Silvy Yuditya; Gifran Rihla Latief (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2022)
The model's ability to optimize student learning, particularly in pencak silat programs, is strongly tied to students' physical education achievement. This study will examine how mastering the bare-handed standard single move affects direct interaction learning model utilization. This study examines direct contact learning model use. A single group was tested pre- and post-testing. This study included elementary school children from Bandung's Soreang District. We randomly selected 80 students as our representative sample in this investigation. According to the results, the direct instruction style improves students' performance on the preliminary and final exams for the bare-handed single stance in pencak silat (4.13>1.73). Keywords: pencak silat, direct instruction model, kujang kencana, bandung regency